HLA‐A promoter, coding, and 3′UTR sequences in a Brazilian cohort, and their evolutionary aspects. (22nd February 2019) - Lima, Thálitta H. A.; Souza, Andreia S.; Porto, Iane O. P.; Paz, Michelle A.; Veiga‐Castelli, Luciana C.; Oliveira, Maria Luiza G.; Donadi, Eduardo A.; Meyer, Diogo; Sabbagh, Audrey; Mendes‐Junior, Celso T.; Castelli, Erick C.
Abstract : HLA‐A is the second most polymorphic locus of the human leucocyte antigen (HLA) complex encoding a key molecule for antigen presentation and NK cell modulation. Many studies have evaluated HLA‐A variability in worldwide populations, focusing mainly on exons, but the regulatory segments have been poorly characterized. HLA‐A variability is particularly high in the segment encoding the peptide‐binding groove (exons 2 and 3), which is related to the antigen presentation function and the balancing selection in these segments. Here we evaluate the genetic diversity of the HLA‐A gene considering a continuous segment encompassing the extended promoter (1.5 kb upstream of the first translated ATG), all exons and introns, and the entire 3′ untranslated region, by using massively parallel sequencing. To achieve this goal, we used a freely available bioinformatics workflow that optimizes read mapping for HLA genes and defines complete sequences using either the phase among variable sites directly observed in sequencing data and probabilistic models. The HLA‐A variability detected in a highly admixed population sample from Brazil shows that the HLA‐A regulatory segments present few, but divergent sequences. The regulatory segments are in close association with the coding alleles. Both exons and introns are highly variable. Moreover, patterns of molecular diversity suggest that the promoter, in addition to the coding region, might be under the same selective pressure, but a different scenario arises when it comes to exon 4 and the 3′UTR segment.